Effects of surfactant on Bacillus mucilaginosus adsorption characteristics during vanadium bioleaching process. Issue 6 (December 2022) - Cai, Zhenlei; Wang, Yue; Zhang, Yimin; Tian, Hongqing
Abstract: Bioleaching is a sustainable and economical technology for extracting valuable elements from low-grade ores or refractory resources. Adsorption of bacteria on mineral surface is the usual basic condition for the deep interaction between bacteria and minerals, thereby improving the bioleaching efficiency of target elements. The addition of surfactants in bioleaching process is an efficient and promising method for improving the bacteria adsorption on mineral surface. Therefore, effects of surfactant SDS (Sodium Dodecyl Sulfate) on bacterial adsorption characteristics were investigated during the bioleaching process from vanadium-bearing shale by Bacillus mucilaginosus (B.M) . The optimal vanadium bioleaching conditions were 0.5 g/L of SDS, 2 g/L of yeast dip powder, and 7.0 of the initial pH. The B.M adsorption equilibrium on the surface of the vanadium-bearing shale with and without addition of surfactant SDS fitted a Freundlich equation, and the addition of surfactant SDS could significantly enhance the B.M absorption on the vanadium-bearing shale. The Pseudo-first-order adsorption kinetics was more suitable to be selected for the demonstration of the B.M adsorption on the surface of the vanadium-bearing shale with and without addition of surfactant SDS, and the addition of surfactant SDS could accelerate the B.M adsorption rate on the surface of the vanadium-bearing shale. Graphical Abstract: ga1 Highlights: Surfactant SDS was employed for improving the vanadium bioleaching effects. The optimal vanadium bioleaching conditions were obtained. The B.M adsorption equilibrium with the addition of surfactant SDS fitted a Freundlich equation. The Pseudo-first-order adsorption kinetics was suitable for the B.M adsorption with the addition of surfactant SDS.